Compassionate Intervention: Addressing Stillbirth in a Persian Cat - Gangwar, Chetna; Saxena, Atul; Singh, Diksha; Kushwaha, Kanchan; Nandanwar, Kalyani; Jajriya, Omprakash; Singh, Akash (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Normal gestation in cats ranges from 61 to 72 days from first day of mating with an average of 65 days (Niyas et al., 2023). It has been noted that after completion of gestation period normally cats take up to 16 h on an average to deliver all her kittens, some cats may even take 4 to 42 h (Root et al., 1995). Dystocia is the inability to expel the foetus through the birth canal without assistance. Incidence of dystocia in cats is quite low as compared to dogs (Gunn-Moore and Thrusfield, 1995), but among cats, Persian cats are more prone to dystocia (Ekstrand and Forsberg, 1994). They show clinical signs like extreme restlessness and vocalization during queening.
Keywords: inability; restlessness; gestation